Human RNA polymerase II subunit hsRPB7 functions in yeast and influences stress survival and cell morphology. - Khazak, V (1995)
Using a screen to identify human genes that promote pseudohyphal conversion in Saccharomyces cerevisiae, we obtained a cDNA encoding hsRPB7, a human homologue of the seventh largest subunit of yeast RNA polymerase II (RPB7). Overexpression of yeast RPB7 in a comparable strain background caused more pronounced cell elongation than overexpression of hsRPB7. hsRPB7 sequence and function are strongly conserved with its yeast counterpart because its expression can rescue deletion of the essential RPB7 gene at moderate temperatures. Further, immuno-precipitation of RNA polymerase II from yeast cells containing hsRPB7 revealed that the hsRPB7 assembles the complete set of 11 other yeast subunits. However, at temperature extremes and during maintenance at stationary phase, hsRPB7-containing yeast cells lose viability rapidly, stress-sensitive phenotypes reminiscent of those associated with deletion of the RPB4 subunit with which RPB7 normally complexes. Two-hybrid analysis revealed that although hsRPB7 and RPB4 interact, the association is of lower affinity than the RPB4-RPB7 interaction, providing a probable mechanism for the failure of hsRPB7 to fully function in yeast cells at high and low temperatures. Finally, surprisingly, hsRPB7 RNA in human cells is expressed in a tissue-specific pattern that differs from that of the RNA polymerase II largest subunit, implying a potential regulatory role for hsRPB7. Taken together, these results suggest that some RPB7 functions may be analogous to those possessed by the stress-specific prokaryotic sigma factor rpoS.